Benefits, safety and outcomes of long-term video EEG monitoring in pediatric patients. (May 2021) - Mann, Catrin; Willems, Laurent M.; Leyer, Anne-Christine; Freiman, Thomas M.; Konczalla, Juergen; Kieslich, Matthias; Rosenow, Felix; Strzelczyk, Adam; Schubert-Bast, Susanne
Abstract: Objective: To investigate benefits of in-hospital, long-term video EEG monitoring (LVEM) for pediatric patients, from a therapeutic perspective and from the perspectives of patients and their families. Methods: A monocentric retrospective cohort study was conducted. Patients aged 0–18 years who underwent LVEM for epilepsy surgery eligibility, epilepsy syndrome clarification, or medication adjustment were evaluated regarding paroxysmal event type, change in seizure frequency and patients' benefits using a standardized evaluation protocol. Results: A total of 163 (88 boys and 75 girls, mean age 10.9 years) pediatric patients underwent 178 LVEM sessions, with a mean duration of 5.4 days. The rate of habitual event detection was 69.1%. Epilepsy diagnosis was confirmed in 147 patients and excluded in 16 patients (9.8%). LVEM results altered the diagnosis of 37.4% of patients. Diagnosis remained unchanged in 49.1% of patients and was specified in 13.5% of patients. Epilepsy surgery was performed in 32 patients, and 64% of epilepsy patients deemed ineligible for epilepsy surgery underwent medication adjustments. Patients or their families found LVEM helpful in 75% of cases. Significant seizure reductions and improvements in the disease course were reported by 45% of epilepsy patients. Three episodes of non-convulsive status epilepticus occurred, representing 1.7% of admissions and 1.9% of patients diagnosed with epilepsy, while no injuries were observed. Conclusions: LVEM is beneficial for pediatric patients from both a medical perspective and from the perspective of patients and their families, even if patients are ineligible for epilepsy surgery. LVEM is well-tolerated with a low risk of status epilepticus and injuries. Highlights: LVEM is useful to classify epilepsy, leading to optimized treatment strategies with positive impact on course of disease. Families considered LVEM to be helpful, even if not eligible for epilepsy surgery. LVEM is well-tolerated with low risk for status epilepticus and no injuries.